A discrete chaotic harmony search-based simulated annealing algorithm for optimum design of PV/wind hybrid system - Askarzadeh, Alireza (Solar energy, 2013)
•A new discrete methodology is used for optimum sizing of PV/wind hybrid system.•The proposed methodology (DCHSSA) is based on simulated annealing algorithm.•DCHSSA merges chaotic search, harmony search and simulated annealing.•DCHSSA yields promising results for the optimum sizing problem. Optimum design of PV/wind hybrid system has become the main focus of many investigations. The ultimate aim of the optimum design is to determine the number of PV panels, wind turbines and batteries so that the total annual cost of the hybrid system subject to some constraints is minimized. The main motivation of this study is to develop a simple but efficient discrete optimization methodology for solving the optimum sizing problem. For this aim, the advantages of three well-known algorithms, namely, chaotic search (CS), harmony search (HS) and simulated annealing (SA), are merged and a novel discrete chaotic harmony search-based simulated annealing algorithm, named DCHSSA, is developed. The proposed methodology is used to find the optimum design of a PV/wind hybrid system. Simulation results indicate the superior performance of the DCHSSA algorithm.